Enhancing the taxonomic resolution of wild grasses and cereal crops of the past through chemotaxonomy of modern and subfossil Poaceae pollen - Katsi, Faidra (2024)
The accurate identification of pollen to species-level from palaeoecological records is essential to refine our understanding of past vegetation change as well as investigating the interaction between past societies and their environments. The grass family, comprising both common wild grasses and cereal crops, poses a unique challenge for taxonomic resolution due to cryptic pollen morphology that prohibits reliable separation between wild grasses and cereals. Low taxonomic resolution of the Poaceae family has contributed to limited use of pollen records in the discussion of the history of agriculture. This thesis explores the application of chemotaxonomy, using Fourier-transform infrared (FTIR) microspectroscopy, to improve taxonomic resolution of Poaceae (grass) pollen samples, on both modern and subfossil samples. Chemotaxonomy, can be described as an alternative method of subfossil classification that uses the inter-species differences among chemical spectra. Prior to the use of chemotaxonomy on subfossil pollen from Lake Nar in Turkey, this method was applied to modern individual pollen grains aiming to test its analytical potential on known observations. The classification algorithm yielded 86% accuracy on species level for acetolysed individual pollen grains suggesting that Poaceae acetolysed sporopollenin carries taxonomical signal strong enough for their classification. The next step was to explore the sensitivity of sporopollenin chemistry to ambient factors. The study showed that the sporopollenin taxonomical signal can be masked by the environmental signal, prohibiting the classification of samples grown in different environments. Since the chemotaxonomy on subfossil samples uses modern reference spectra to classify subfossil sporopollenin based on the “closest match” it became clear that the modern analogues should include spectra that capture past plant diversity and environs. The final data chapter describes the application of chemotaxonomy to subfossil samples. The chemotaxonomic classifications overrepresented cereal crops compared to traditional light microscope identifications. This difference was explained by the nature of the modern reference spectra library that was dominated by cereal species and included plants probably grown in stressed conditions. The application of chemotaxonomy to subfossil Poaceae pollen, as demonstrated in this thesis, provides valuable insights into the potential and limitations of this method for enhancing taxonomic resolution in the palaeoecological record. This thesis is not a complete study on the application of chemotaxonomy in subfossil contexts, it is rather the beginning of it. However, it has shown an alternative approach to tackle pollen taxonomic difficulties for one of the most widespread and economically important plant families.